2016
DOI: 10.15171/jlms.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antimicrobial Photodynamic Therapy as an Adjunctive to Mechanical Debridement in the Treatment of Peri-implant Diseases: A Randomized Controlled Clinical Trial

Abstract: Introduction:The purpose of the present study was to assess the clinical effects of antimicrobial photodynamic therapy (PDT) after closed surface scaling in the treatment of peri-implant diseases. Methods: Ten patients with a total of 15 pairs of dental implants, showing clinical and radiographic signs of peri-implant diseases, were included in this study. In each patient, one implant randomly served as control implant and the other served as test implant. The control implants were treated with closed surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…In the present study, no AE was observed in any patient of the two groups. This is in agreement with the reported safety profile of PVD . Nevertheless, once again, due to the wide choice of lasers and photosensitizers available on the market, different combinations should be explored to determine the safety profile of each one.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the present study, no AE was observed in any patient of the two groups. This is in agreement with the reported safety profile of PVD . Nevertheless, once again, due to the wide choice of lasers and photosensitizers available on the market, different combinations should be explored to determine the safety profile of each one.…”
Section: Discussionsupporting
confidence: 87%
“…As observed in the control group and as supported by the literature, mechanical cleaning and rinsing can control peri‐implantitis to some extent, but the outcomes are unsatisfying in many patients. Clinical trials showed that PDT after surface scaling improved the outcomes of patients with peri‐implantitis . PDT combined with some forms of mechanical debridement can be used for the management of peri‐implantitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different treatment protocols for peri-implantitis have been studied, including chemical and mechanical intervention strategies [10,25,26]. Considering the increasing use of natural products, we have show that Brazilian red propolis hydroalcoholic extract have inhibitory effect on mono-species biofilms of Candida albicans and co-culture biofilms of C. albicans and C. glabrata developed on titanium surfaces.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of those microorganisms, in association with deficient hygiene, can induce a harmful microenvironment, in which the multispecies communities can release toxins and by-products that makes treatment unsuccessful [8]. Therefore, some clinical procedures have been proposed, including abrasive therapies with air, water, sodium bicarbonate, citric acid, plastic curettes scraping, ultrasonic cleansing, among others [9,10]. However, none of those methods have obtained satisfactory results [8].…”
Section: Introductionmentioning
confidence: 99%